THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE, WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE NORTH SUMATRA NATIONAL UNITY AND POLITICS AGENCY OFFICE - Eka Anugrah Pandia; Lely Winda Pasaribu; Gabriella Christi; Faisal Akbar (CV. Radja Publika, 2026)
This study was conducted to determine whether there is an influence caused by factors of the Work Environment, Work Discipline, and Work Motivation at the National Unity and Politics Agency office in North Sumatra located on the road to Employee Performance. From this study we obtained 62 people as our research subjects. Our data collection technique that we used was the distribution of Questionnaires (Surveys) so that the data obtained showed that our sample was predominantly Generation Z (Born 1997-2012) as many as 48 people and the rest by the generation below or above. The results of the study revealed that partially the Work Environment and Discipline have a positive effect and show significant changes on Employee Performance while Work Motivation does not affect Employee Performance. Simultaneously, the Work Environment, Work Discipline, and Work Motivation have a positive and significant effect on Employee Performance.